Cara Menghadapi Siswa yang Malas dan tidak Semangat Belajar - Abdul Hadi; Moh Nabil Rafif Awwal; Chalid Maulana Nizar (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The phenomenon of students displaying lazy attitudes and a lack of learning motivation represents a major challenge in the teaching and learning process of Islamic Religious Education (PAI) in various schools across Indonesia. This condition has a direct impact on low levels of student engagement and the achievement of expected learning objectives. This article provides an in-depth analysis of the multidimensional causes of this phenomenon, including internal student factors such as learning interest, levels of self-efficacy, intrinsic motivation, and learning styles, as well as external factors encompassing the role of teachers, particularly in the selection of instructional methods, classroom management, and pedagogical interactions. In addition, the family environment, peer influence, and digital culture are also important factors affecting students’ learning motivation. The article also presents various practical and integrated strategies that can be implemented by PAI teachers to enhance students’ learning motivation. The proposed approaches include strengthening value-based classroom management rooted in Islamic principles, applying active, participatory, and contextual learning methods, and reinforcing collaboration between schools and families in building a positive learning culture. Using a descriptive qualitative approach and classroom action research (CAR), the analysis shows that teachers’ emotional engagement, the implementation of educational reward systems, reflection on religious values, and experiential learning are able to increase students’ intrinsic motivation. This study implies the importance of curriculum innovation and strengthening professional development for PAI teachers to better orient learning toward fostering students’ enthusiasm for learning and the sustainable development of religious character in the digital era.